Evolución de la producción de pastos mejorados en la dehesa extremeña en año seco - Espejo, Diaz; Martin Bellido, M (Pastos, 1987)
It is studied the influence of the type of pastures (pasture implemented with subterranean clover and natural pasture), variability, frequency of cuts starting date, cuts high on the annual and monthly production of DM/ha under environmental "dehesa" conditions in Extremadura, Spain, during a climatological adverse year. The first two factors have not significant differences. The subterranean clo- ver pasture produced more than doubled than natural pasture being significant the differences between locations within this type of pastures. The monthly cut produced 40% less when the distance between cuts was longer, this drop was mainly produced in March. The figures of distribution of the production are shown. They present a má- ximum in March, falling in April because of the cold weather and lack of rain. Natural pasture production is restricted to the months of February to April whe- reas the subterranean clover pasture began production in November. Key
Keywords: Climatology; Dehesa; Grass production figures; Subterranean clover